Outcome of management of tibial plateau fracture by posterior Lobenhoffer approach: case series - Jamil Khattak, Mujahid; Rufina Ali; Yasir Mohib (Journal of the Pakistan Medical Association, 2023)
Displaced Tibiai plateau fractures are complex periarticular injuries. Restoration of the anatomy and internal fixation are key elements for early return to function and better functional outcome. Newer modalities like CT scans has enabled better understanding of these fractures. Posterior approaches were not very common as compared to anteromedial and anterolateral surgical approach. Posterior approach has the advantage of avoiding anterior skin and soft tissues that has been compromised as a result of the fracture; it is also particularly helpful in direct and accurate reduction in certain fracture patterns. This case series highlights the importance of posterior approach to restore the articular surface of complex periarticular proximal Tibial fractures. All displaced tibial plateau fractures with posteromedial fragment were included in the study. Pathological fractures and all open fractures were excluded from this study. ---Continue